PRIMEIRO REGISTRO DE ð˜—ð˜©ð˜°ð˜³ð˜¢ð˜¤ð˜¢ð˜¯ð˜µð˜©ð˜¢ ð˜´ð˜¦ð˜®ð˜ªð˜±ð˜¶ð˜¯ð˜¤ð˜µð˜¢ð˜µð˜¢ (FABRICIUS, 1775) (COLEPOTERA, CERAMBYCIDAE) NO ESTADO DE SÃƒO PAULO - Berti Filho, Evoneo; Cerignoni, JoÃ£o Angelo; Souza JÃºnior, Carlos Nogueira (REVISTA DE AGRICULTURA, 2020)
PRIMEIRO REGISTRO DE ð˜—ð˜©ð˜°ð˜³ð˜¢ð˜¤ð˜¢ð˜¯ð˜µð˜©ð˜¢ ð˜´ð˜¦ð˜®ð˜ªð˜±ð˜¶ð˜¯ð˜¤ð˜µð˜¢ð˜µð˜¢ (FABRICIUS, 1775) (COLEPOTERA, CERAMBYCIDAE) NO ESTADO DE SÃƒO PAULO